In situ effects of urban river pollution on the mudsnail Potamopyrgus antipodarum as part of an integrated assessment - Zounkova, Radka; Jalova, Veronika; Janisova, Martina; Ocelka, Tomas; Jurcikova, Jana; Halirova, Jarmila; Giesy, John P; Hilscherova, Klara (Aquatic toxicology, 2014)
The freshwater mudsnail (Potamopyrgus antipodarum) is sensitive to toxicity of both sediment and water and also to the endocrine disrupting compounds (EDC) at environmentally relevant concentrations. This study determined effects of in situ exposure of P. antipodarum as a part of a complex assessment of the impact of a city metropolitan area with large waste water treatment plant (WWTP) for 0.5 million population equivalents on two urban rivers. The study combined the in situ biotest with detailed chemical analyses and a battery of in vitro bioassays of both sediment and water. Passive sampling of river water was conducted during the course of exposure of the mudsnail. P. antipodarum was exposed for 8 weeks in cages permeable to sediment and water at localities up- and down-stream of the city of Brno, Czech Republic and downstream of the WWTP in two rivers. Greater mortality and significantly decreased embryo production of P. antipodarum were observed immediately downstream of the city of Brno. P. antipodarum exposed at locations downstream of the metropolitan area and WWTP exhibited greater mortality, while numbers of embryos produced by surviving individuals were comparable or slightly greater than for individuals held at the least polluted location. Comparisons with results of chemical analysis and in vitro assays indicate occurrence of groups of compounds contributing to observed effects. Differences in mortalities of mudsnails among sites corresponded well with in vitro cytotoxicity and concentrations of metals. The results of this study confirm the applicability of this novel field biotest with P. antipodarum for the evaluation of the effects of river pollution on metazoans, especially as suitable in situ part of integrative contamination assessment.
Keywords: Animals; rozmnožování; geologické sedimenty; Inhibitory Concentration 50; chemické látky znečišťující vodu; Cell Line, Tumor; Mortality; Urban Population; Water Pollutants, Chemical; monitorování životního prostředí; Reproduction; lidé; Survival Analysis; Rivers; inhibiční koncentrace 50; mortalita; řeky; městské obyvatelstvo; Environmental Monitoring; analýza přežití; Geologic Sediments; Snails; zvířata; hlemýždi; nádorové buněčné linie; Humans